The impact of specialization, ownership, competition and regulation on efficiency: a case study of Indian seaports - Nicole Adler; Georg Hirte; Shravana Kumar; Hans-Martin Niemeier (Maritime Economics & Logistics, 2021)
We develop a two-stage formulation to estimate seaport performance and to understand the drivers of efficiency, which could potentially include specialization, ownership, competition and tariff regulation. The first-stage non-parametric, slacks-based measure estimates the technical efficiency of each port. For the second-stage analysis, we develop a set of contextual variables including an absolute measure of specialization and a berth-level measure of ownership structure. To measure competition, we develop spatial measures that quantify the level of competition as a function of distance. We subsequently apply this formulation to major Indian seaports, covering a period of 21~years, from 1995 to 2015. The first-stage results suggest that average seaport efficiency has increased gradually over time. The second-stage fixed effects regressions show that specialization and external stakeholder participation have significant positive impacts on seaport performance. Perhaps surprisingly, we find that, in a tiered governance framework, competition between major seaports and local seaports has a significant negative impact on performance, potentially due to excessive infrastructure. Finally, changes in the regulatory mechanism over time are shown to be efficiency improving.
Keywords: 380; Indian seaports; Technical efficiency; Specialization; Ownership; Competition; Tariff regulation